Pelatihan Analisis Data Menggunakan Aplikasi Statistik SPSS - Retno Marsitin; Nyamik Rahayu Sesanti (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2022)
The rapidly growing digital era demands everyone to master technology, especially students. Students are required to be technology literate, but there are still many students who are not technology literate, so they are not optimal in utilizing technology, especially in data analysis. The solution to these problems is holding service activities in the form of data analysis training using the SPSS statistical application with socialization, training and mentoring, presentations, discussion forums, and evaluations. The training activities with modules explained in detail the steps for entering data input, operating, and analyzing with examples of data, and data analysis exercises that were presented in an interesting way so that the students were not boring. Students were actively involved during the activity until the end of the activity and evaluation. This activity aims to improve the quality of students in data analysis using the SPSS statistical application. This training activity received a positive response, and the students were always active in participating in the activity until it was completed, so it can be concluded that the training activity was carried out very well and succeeded in accordance with the goals and targets set.